Urgensi Pendidikan Bela Negara di Era Society 5.0 (Tantangan dan Peluang) - Rasona Sunara Akbar; Halba Alfath Afwa Ashari; Jatra Putra Suharsono; Ghina Ramadanti; M Rizky Apriansyah; Heny Sulistiyawan; Kiagus Daffa Triandeda (Journal on Education, 2024)
This research aims to examine the urgency of national defense education in the Society 5.0 era, with a focus on the challenges and opportunities faced. The research background reflects the importance of maintaining state sovereignty and building awareness of state defense in the midst of increasingly complex globalization. The research method used is a qualitative approach with document analysis and interviews as data collection techniques. The research results show that national defense education which is integrated into the citizenship education curriculum has an important role in shaping students' character and fostering a spirit of love for the country. The main challenge in its implementation is overcoming the influence of globalization which can damage national values. However, there are opportunities to optimize national defense education by utilizing developments in information and communication technology. In conclusion, state defense education is a vital aspect in maintaining state sovereignty and preparing the young generation as agents of change in the Society 5.0 era.